Characterization, agricultural potential, and perspectives for management of light soils in Brazil - Donagemma, Guilherme Kangussu; Freitas, Pedro Luiz de; Balieiro, Fabiano de Carvalho; Fontana, Ademir; Spera, Silvio Túlio; Lumbreras, José Francisco; Viana, João Herbert Moreira; Araújo Filho, José Coelho de; Santos, Flávia Cristina dos; Albuquerque, Manoel Ricardo de; Macedo, Manuel Cláudio Motta; Teixeira, Paulo Cesar; et al. (Pesquisa Agropecuaria Brasileira, 2016)
Light soils occupy 8% of the Brazilian territory and are especially expressive in the new and last agricultural frontier in Brazil: the Matopiba region – in the states of Maranhão, Tocantins, Piauí, and Bahia –, where they represent 20% of the area. These soils fit into the textural classes of sand, loamy sand, and sandy loam, down to 0.75-m soil depth or deeper, and they are mainly represented by Entisols (Quartzipsamments), and partly by Oxisols and Ultisols. The understanding of soil functioning depends on the establishment of distinguishing criteria for: organic matter dynamics; content and mineralogy of the clay fraction; coarse sand and total sand contents, in relation to those of fine sand; mean diameter of the sand fraction; and water retention capacity. These criteria can contribute for the zoning and for the conservationist and fertility management of light soils, as well as for the estimation of their agricultural potential. Integrated production systems, such as, crop-livestock and crop-livestock-forestry integration, besides no-tillage with crop rotation, mixed forestry planting with legumes, and the use of green manure and cover crops, are relevant for the proper management of these soils. The objective of this review was to characterize light soils and to highlight the main challenges regarding their agricultural potential and their conservation and fertility managements, in face of the expansion and consolidation of the new Brazilian agricultural frontier.
Keywords: agricultural aptitude; management and conservation; soil fertility management; Entisols (Quartzipsamments); sandy soils; fragile soils